Estudio de prefactibilidad para la instalación de una planta de bloqueadores solares con óxido de zinc y dióxido de titanio - Schmitt Olcese, Walter Hipolito (2020)
The alternative to protect yourself from UV rays and prevent serious injuries and even skin cancer is in sunblock, also called physical screens. This product, due to its characteristics, has high resistance and durability over time, unlike sunscreen, which is commonly used and does not offer the effectiveness of the first but is used due to its low cost and due to the lack of information that exists in this regard. Considering the need to have an effective product for the prevention and care of the skin, our objective is to determine the feasibility and viability of the operation process and launch to the market of a 100% Peruvian brand sunblock that contains oxide zinc and titanium dioxide. This research includes a pre-operational year (2020) and five operational years (2021 to 2025). It takes place in Lima department and the plant’s location is in the Lince district. Likewise, the variables market size, productive resources, technology and equilibrium point are evaluated to determine the project plant size. In addition, the laboratory's production capacity is analyzed (156 325 units) and the processes and technologies necessary to manufacture the product and the steps to safeguard product quality are defined. Also, the required investment is determined, which amounts to 146 122 soles and presented other aspects as: operating costs; income and expenses budget, results statements and financial situation. On the other hand, the project’s financial evaluation indicators are established: VANF (336 992 soles), TIRF (85%), and COK (18%). Finally, a project’s social evaluation is carried out where the areas and communities of influence are identified and the project’s added value is calculated: 2 444 190 soles.